2018
DOI: 10.1093/jisesa/iey128
|View full text |Cite
|
Sign up to set email alerts
|

Thiamethoxam, Clothianidin, and Imidacloprid Seed Treatments Effectively Control Thrips on Corn Under Field Conditions

Abstract: With the widespread adoption of no-tillage technology, outbreaks of thrips have caused serious damage to summer corn fields in China. Therefore, effective control of pest populations is often essential for cost-effective crop production. In this study, experiments were conducted in 2014 and 2015 to determine the control efficacy of seven neonicotinoid insecticide seed treatments against corn thrips and the effects of these treatments on natural enemy population densities and emergence rates, seedling character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 37 publications
4
7
0
1
Order By: Relevance
“…These results are similar to those reported by Ding et al. (2018) where seed treatment with 1.0 or 2.0 mg a.i. kernel −1 clothianidin increased the height, growth index, and root length of seedlings in a field study in China.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are similar to those reported by Ding et al. (2018) where seed treatment with 1.0 or 2.0 mg a.i. kernel −1 clothianidin increased the height, growth index, and root length of seedlings in a field study in China.…”
Section: Discussionsupporting
confidence: 93%
“…The increase in growth stage, height, and root surface area in the current study suggests treatment with clothianidin + B. firmus increased early season growth in corn. These results are similar to those reported by Ding et al (2018) where seed treatment with 1.0 or 2.0 mg a.i. kernel −1 clothianidin increased the height, growth index, and root length of seedlings in a field study in China.…”
Section: Discussionsupporting
confidence: 92%
“…These two insecticides were recently labeled as a seed treatment for controlling FAW and exhibited a high level of control efficacy against this species ( Zhang P. et al, 2016 ; Pes et al, 2020 ). Neonicotinoid insecticides such as CLO and THI have been widely used as seed treatments in multiple crops and exhibit good activity against a broad range of pests including aphids ( Zhang P. et al, 2016 ; Zhang Z. et al, 2016 ), whiteflies ( Zhang et al, 2011 ), and thrips ( Reisig et al, 2012 ; Ding et al, 2018 ). To the best of our knowledge, there are no prior studies assessing the efficacy of diamides in combination with neonicotinoids for FAW larval control as seed treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were different from those reported by Abdu-Allah and Hashem (2017) and Huang et al (2015) but consistent with studies showing that neonicotinoid seed treatments could promote seed germination and increase primary root length, weight, and height of corn seedlings ( Horii et al, 2007 ; Duan et al, 2012 ; Zhang et al, 2015 ). The stimulation of growth parameters may be the result of improved activity of antioxidants and stress-related enzymes such as guaiacol peroxidase and glucose-6-phosphate dehydrogenase ( Ding et al, 2018 ). Previous studies have shown that insecticides, especially neonicotinoids, cause a decline in natural enemies and pollinators ( Moser and Obrycki, 2009 ; Bredeson and Lundgren, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Isto pode ter ocorrido devido à hidroxilação da ponte de etileno no anel de imidazolinidina, redução do grupo nítrico ou oxidação do imidaclopride em álcool 6-cloropicolítico (SUR;STORK, 2003). Por outro lado, o tiametoxam pode se decompor em clotianidina, o que pode contribuir para sua atividade contínua na planta e maior efetividade no controle de insetos (DING et al, 2018).…”
Section: Discussionunclassified